New Evidence of LiO2 Dismutation in Lithium–Air Battery Cathodes - del Pozo, Maria (2016)
The dismutation of electrochemically generated soluble lithium superoxide with the formation of a lithium peroxide deposit on Au has been studied by addition of lithium ions and following the mass uptake detected by the electrochemical quartz crystal microbalance at the open-circuit potential and the surface morphology evolution by using atomic force microscopy.